Application Of Fcaw Welding Techniques In Supply Boat Manufacturing At Pt Vallianz - Arvian Enggal Putra; Fardin Hasibuan (METALOGRAM, 2025)
FCAW is a semi-automatic welding method that offers advantages in welding speed, weld quality, and flexibility in various welding positions. The process begins with equipment preparation, selecting welding parameters according to the Welding Procedure Specification (WPS) standard, and then carrying out welding using root pass, fill pass, and cap pass techniques. Evaluation of welding results is carried out through visual inspection and non-destructive testing (NDT), such as Magnetic Particle Inspection (MPI) and Ultrasonic Thickness Testing (UT) to ensure the quality and integrity of the joint. The results show that the FCAW method is highly effective in supply boat fabrication, especially when supported by good work procedures, adequate operator skills, and strict quality control. This research is expected to provide a practical overview and serve as a reference for students and industry in implementing welding technology in the shipping sector.